MOBILE PAYMENT ADOPTION INTENTION DURING PANDEMIC COVID-19 IN INDONESIA - Dewi Mustikasari Immanue; Yuli Kartika Dewi (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
Essentially, the fast development of technology, especially the internet, has created a shift in consumer behaviour with regards to shopping that has leaned toward online shopping. This drives the sprouting of many different types of mobile payment (M-payment) that can be used as a payment tool. Moreover, the world is currently facing the COVID-19 pandemic, in addition, Indonesia is currently doing a mass scale social distancing (PSBB) to stop the infection of COVID-19, among other things limiting out of the home movement, and practicing physical distancing. This appeal makes shops advising payments using M-payment or cashless. Hence, the main purpose of this study is to identify the impact of the COVID-19 pandemic on consumer attitude in Indonesia specifically in the adoption of mobile payment (M-payment) as the safe way to do payments. The assumption of M-payment adoption is based on situational influences, personal knowledge, and perceived usefulness. The research model has been empirically tested using 217 responses from a field questionnaire conducted in a number of large cities in Indonesia – by using the multiple regression analysis techniques. The findings of the study reveal that situational influences, personal attitude, personal knowledge have a significant effect on M-payment adoption in this global pandemic of Covid-19. Meanwhile, perceived usefulness has no significant effect on M-payment adoption in this global pandemic of Covid-19. A suggestion for the M-payment providers, despite PU having no significant effect, it continues to be one of the drawing factors for people to use M-payment, hence it’s best for the M-payment to continue providing benefits to its users to increase cashless payment in order to stop the spread of COVID-19. Why is it important to continue providing benefits for users? Because this study has shown that personal attitudes and personal knowledge have a significant effect on the interest of M-payment users, which means during this COVID-19 pandemic, positive attitude and people’s knowledge regarding M-payment has been shaped due to the situation, therefore, by continuously providing benefits, M-payment platforms could increase the number of people using M-payment.